Beneficial rhizobacteria immobilized in nanofibers for potential application as soybean seed bioinoculants - de Gregorio, Priscilla Romina (2017)
Seed inoculation with plant growth promoting rhizobacteria (PGPR) is an ideal tool to supply the soil with a high density of beneficial microorganisms. However, maintaining viable microorganisms is a major problem during seed treatment and storage. In this work, an evaluation was made of the effect of bacterial immobilization in nanofibers on the stability (viability and maintenance of beneficial properties) of two potential PGPR, Pantoea agglomerans ISIB55 and Burkholderia caribensis ISIB40. Moreover, the impact of soybean seed coating with nanofiber-immobilized rhizobacteria on bacterial survival during seed storage and on germination and plant growth parameters was determined. Bacterial nanoimmobilization and subsequent seed coating with nanofiber-immobilized rhizobacteria were carried out by electrospinning. The results demonstrate that this technique successfully immobilized P. agglomerans ISIB55 and B. caribensis ISIB40 because it did not affect the viability or beneficial properties of either rhizobacteria. Seed coating with nanofiber-immobilized rhizobacteria improved P. agglomerans ISIB55 and B. caribensis ISIB40 survival on seeds stored for 30 days and contributed to the successful colonization of both bacteria on the plant root. Moreover, seed coating with P. agglomerans ISIB55 increased germination, length and dry weight of the root. Furthermore, seed coating with B. caribensis ISIB40 increased leaf number and dry weight of the shoot. Therefore, the technique applied in the present work to coat seeds with nanofiber-immobilized PGPR could be considered a promising eco-friendly approach to improve soybean production using a microbial inoculant.